Load model of ball mill based on power spectrum analysis - ZHANG Jie; WANG Jian-min; YANG Zhi-gang; LI Yan-jiao (Gong-kuang zidonghua, 2013)
The paper built load model of ball mill based on power spectrum analysis, and analyzed relations among ball mill load, sound intensity of mill noise and spectrum distribution of mill noise, that is sound pressure of detection point of mill noise is proportional to square of vibration speed of ball mill shell, noise frequency is proportional to vibration frequency of ball mill shell, mill noise signal become weaken gradually with increasing of ball mill load. Spectrum of mill noise mainly distributes under 1 500 Hz. Distribution of spectrum of mill noise is more uniform when the ball mill runs normally, and spectrum of mill noise mainly distributes 0~1 000 Hz when the ball mill runs in undergrinding. Matlab simulation result validates feasibility and effectiveness of the load model of ball mill.